Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1634/theoncologist.11-8-887
|View full text |Cite
|
Sign up to set email alerts
|

Thymoma: Benign Appearance, Malignant Potential

Abstract: Thymoma is a rare tumor with a largely indolent growth pattern. It does, however, have malignant potential as a result of its ability to invade locally and metastasize regionally. Often associated with a number of immuneand nonimmune-mediated paraneoplastic syndromes, patient outcomes are directly related to stage of disease and the ability to achieve a complete surgical resection. Surgery is the mainstay of treatment, with adjuvant radiation recommended for invasive thymoma. Sensitive to both chemotherapy and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
50
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 61 publications
1
50
0
Order By: Relevance
“…Anti-muscle-specific tyrosine kinase antibody testing is also used in diagnosing seronegative myasthenia gravis [10] . Around 75% of the patients with myasthenia gravis exhibit thymic abnormalities, and it has been suggested that the pathogenesis of the disease starts in the thymus: 60-70% have thymic hyperplasia and 10-15% have a thymoma [1,3,4,11] .…”
mentioning
confidence: 99%
“…Anti-muscle-specific tyrosine kinase antibody testing is also used in diagnosing seronegative myasthenia gravis [10] . Around 75% of the patients with myasthenia gravis exhibit thymic abnormalities, and it has been suggested that the pathogenesis of the disease starts in the thymus: 60-70% have thymic hyperplasia and 10-15% have a thymoma [1,3,4,11] .…”
mentioning
confidence: 99%
“…For example, our present study showed that only clinical stage is an independent prognostic factor, as compared to pathological classification and completed resection. In addition, although thymoma is basically indolent in its early stage, certain investigators asssert that occasionally benign-appearing thymoma is potentially malignant (25,26). Furthermore, clinical doctors have not achieved a standardized solution to classify thymoma into typical TMN classifications.…”
Section: Discussionmentioning
confidence: 99%
“…CT allows for the characterization of tumour and describes possible invasion into surrounding structures. 6 High-resolution CT is helpful for the detection of pulmonary abnormalities, especially fast progressive bronchiectasies which are very frequent in Good's syndrome patients. 7 Such a picture was present in our patient.…”
Section: Discussionmentioning
confidence: 99%